1991
DOI: 10.3109/10826089109058918
|View full text |Cite
|
Sign up to set email alerts
|

Perceived Risk and Sources of Information Regarding Cocaine

Abstract: A study was made of the perceptions of risk and of the sources of information about risk regarding cocaine. Subjects were adult (N = 90) and juvenile (N = 20) cocaine abusers in seven Baltimore area treatment programs. Using structured interview, it was found that 87.8% of adults and 80.0% of youth had experienced at least one negative consequence of their cocaine use, other than addiction, prior to entry into treatment. The most common negative experience reported by both groups was the loss of reality testin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
1
0

Year Published

1992
1992
2007
2007

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 8 publications
1
1
0
Order By: Relevance
“…This concurs with studies performed by Gonzalez and Haney [ 13 and Hickey [2], who found a fundamental problem existing in the United States in regards to alcohol use. The general perception of alcohol as a socially acceptable drug in the United States causes it to be seen as a benign substance by college students.…”
Section: Discussionsupporting
confidence: 93%
“…This concurs with studies performed by Gonzalez and Haney [ 13 and Hickey [2], who found a fundamental problem existing in the United States in regards to alcohol use. The general perception of alcohol as a socially acceptable drug in the United States causes it to be seen as a benign substance by college students.…”
Section: Discussionsupporting
confidence: 93%
“…Empirical studies show low perceived risk is correlated with unsafe sexual behavior, increased rates of STDs and HIV, tobacco use, and multi-substance misuse [29 -31]. Perceived risk was a significant predictor of alcohol, marijuana, and cocaine use in college students [32,33], but researchers have not assessed perceived risk of substance use and sexual activity in student athletes.…”
mentioning
confidence: 99%